ANALISIS KEBIJAKAN PEMERINTAH KABUPATEN SRAGEN DALAM MENEGAKKAN HUKUM TERHADAP KETIDAKPATUHAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN - Rizka Rizka; Hafidz Nur Firdaus (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
In writing this law, it aims to analyze regarding the policy of the Sragen Regency Government in enforcing the law for non-compliance with PBB-P2 payments and would like to know what obstacles are the factors for community non-compliance in paying PBB-P2. The research method in writing this law is an empirical legal research method that focuses on analyzing the legal reality in the form of tax arrears owed due to public disobedience in paying taxes, then related to whether or not law enforcement is effective based on legislation and the theory of law enforcement factors. In writing this law, it shows the results that law enforcement against public disobedience in paying PBB-P2 in Sragen Regency is still less than optimal, this is evidenced by the increase in the number of tax arrears from 2018 - 2020 and  two tax whitening policies which result in ineffective provision of taxes. administrative sanctions in the form of tax fines so that the Regional Regulations related to PBB-P2 need a change regarding law enforcement in the form of tax collection to become more active as a form of firmness of the Sragen Regency Government in enforcing the law against non-compliance with PBB-P2 payments.